Protective efficacy of Solanum xanthocarpum root extracts against free radical damage: phytochemical analysis and antioxidant effect - Kumar, S.; Sharma, U. K.; Sharma, A. K.; Pandey, A. K. (Cellular and Molecular Biology, 2012)
Free radicals have been implicated in many diseases. They attack biological macromolecules in healthy human cells and cause protein and DNA damage along with lipid peroxidation. Present study reports the phytochemical analysis as well as free radical scavenging and antioxidant activities of Solanum xanthocarpum root extracts. Tannins, flavonoids, terpenoids, alkaloids, saponins and steroids were present in different extracts. Total flavonoid content in extracts was quantified and maximum contents were found in ethyl acetate fraction followed by chloroform and ethyl alcohol fractions, respectively. Dose dependent response was observed in metal ion chelating activity of extracts. Comparatively better chelating activity was found in polar extracts. Most of the extracts exhibited significant free radical scavenging activity in DPPH radical scavenging assay. Ethanolic and aqueous extracts accounted for about 40-50% lipid peroxidation inhibition (LPOI) in rat liver homogenate. Antioxidant activity did not show direct correlation with the amount of flavonoid contents in the extracts. However, direct correlation was observed between DPPH free radical scavenging activity and LPOI. Antioxidant activity of the extracts was compared with standard antioxidants. The differential activity observed in extracts could be attributed to the presence of other phytochemicals such as tannins and terpenoids in addition to flavonoids. The study demonstrated appreciable protective efficacy in S. xanthocarpum root extracts against free radical damage.